The Dynamics Shaping Profitability in the Turkish Banking Sector: An Empirical Assessment - Aliyeva, Lale; Kayadibi, Saim (Faculty of Economics and Management, 2025)
This study empirically examines the key determinants of bank profitability in the Turkish banking sector from 2001 to 2023. Recognizing the sector’s pivotal role in macroeconomic stability and financial intermediation, the analysis employs second-generation panel econometric techniques to explore both the long-run and short-run dynamics influencing profitability. Drawing on a comprehensive dataset covering 25 banks, the study utilizes return on assets (ROA) as the dependent variable. It considers capital adequacy, deposit-to-asset ratio, loan-toasset ratio, and non-interest income as core explanatory variables. The findings reveal robust and statistically significant long-run relationships between all explanatory variables and bank profitability. Capital adequacy emerges as the most influential determinant, underscoring the strategic importance of robust capitalization in ensuring resilience and sustained performance. In the short term, while non-interest income continues to exert a positive impact, deposit mobilization exhibits a temporary adverse effect reflecting the complexities of funding costs in Türkiye’s inflationary environment. The use of both Pooled Mean Group (PMG) estimation and Fully Modified OLS (FMOLS) enhances the credibility and robustness of the results. These findings underscore the importance of maintaining strong capital buffers, managing deposit structures effectively, supporting sustainable credit growth, and fostering income diversification through digital and non-traditional banking services. The study provides valuable insights for bank managers, regulators, and policymakers seeking to enhance the profitability and resilience of the Turkish banking system in the face of evolving macroeconomic and structural challenges.